Evaluation of the effect of solid and cationic lipids on siRNA delivery systems - Oner-Bozkurt, Ezgi (My University, 2020)
This study aims to develop nanoparticles with different types of solid and cationic lipids and evaluate them as siRNA delivery systems. For this purpose, we prepared a series of lipid nanoparticles by combining cationic lipids (DOTMA, stearylamine, DDAB, and Esterquat-1) with solid lipids [Precirol ATO 5 (P), Compritol 888 ATO (C), Cetyl palmitate 15 (CP15)] by a modified hot microemulsion method. The developed cationic solid lipid nanoparticles (cSLNs) were characterized in terms of particle size, size distribution, and zeta potential using a Malvern NanoZS Instrument. After determining the complexation ability of cSLNs with siRNA, the Resazurin assay was conducted to evaluate and compare their cytotoxicity. The cSLNs which successfully bind siRNA and show low cytotoxicity were further investigated by in vitro cellular uptake (fluorescence microscopy) and gene silencing (Western Blot) studies. According to characterization measurements, all formulations had a small particle size (< 200 nm), narrow size distribution (polydispersity index, PDI< 0.5), and high positive zeta potential (> +25 mV). The cSLN with Esterquat-1 was eliminated from further studies due to the poor complexation capacity. The use of cSLN with stearylamine was found inappropriate because of its high toxicity on both DU145 and PC-3 prostate cancer cells. None of these formulations showed effective gene silencing on DU145 cells. Only cSLN including P:C mixture with DDAB or DOTMA were uptaken by PC-3 cells and showed silencing efficiency. This study shows the importance of the lipid type selection for siRNA delivery systems and how this changes the transfection efficiency of these systems.
BioTurkey International Biotechnology Congress
Keywords: Cationic solid lipid nanoparticles; cytotoxicity; gene delivery systems; RNA interference; siRNA; transfection efficiency; Cancer; Genes & Society; Nanoscience & Materials; CANCER; Drug Delivery Systems; Gene therapy; Nano Biotechnology; NanoMedicine; Prostate cancer